2021
DOI: 10.1002/pa.2761
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of COVID‐19 pandemic on global stock markets: Return, volatility, and bad state probability dynamics

Abstract: This study investigates the impact of COVID‐19 pandemic on stock returns, conditional volatility, conditional skewness and bad state probability. This study utilizes an asymmetric exponential generalized autoregressive conditional heteroscedasticity model to capture the asymmetric effect of positive and negative shocks (news) on conditional volatility. Using a sample consisting of international stock market indices in Brazil, China, Italy, India, Germany, Russia, Spain, United Kingdom, and United States, over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 52 publications
2
19
0
3
Order By: Relevance
“…Our study is also close to Basuony, Bouaddi, Ali and EmadEldeen (2021) who, using data that include the covid-19 crisis period, report increased conditional volatilities, which are not symmetric across international stock markets: they find that negative effects of covid deaths were accentuated relative to positive effects of covid recoveries. Their study uses asymmetric EGARCH, allowing them to examine the differential effects of negative and positive shocks on conditional variance and skewness but, unlike our study, does not establish whether developing markets were affected the same way as developed markets or which one of covid infections, management, or death had greater effects on stock returns and bond yields; indeed, their study focuses only on the stock markets.…”
Section: Motivationsupporting
confidence: 77%
“…Our study is also close to Basuony, Bouaddi, Ali and EmadEldeen (2021) who, using data that include the covid-19 crisis period, report increased conditional volatilities, which are not symmetric across international stock markets: they find that negative effects of covid deaths were accentuated relative to positive effects of covid recoveries. Their study uses asymmetric EGARCH, allowing them to examine the differential effects of negative and positive shocks on conditional variance and skewness but, unlike our study, does not establish whether developing markets were affected the same way as developed markets or which one of covid infections, management, or death had greater effects on stock returns and bond yields; indeed, their study focuses only on the stock markets.…”
Section: Motivationsupporting
confidence: 77%
“…Penelitian yang dilakukan oleh (Basuony, Bouaddi, Ali & Emadeldeen, 2021) menjelaskan bahwa Kasus Kematian COVID-19 memiliki hubungan negatif dengan pengembalian saham di Italia dan hubungan tidak signifikan pada negara lainnya. Kasus Sembuh COVID-19 memiliki pengaruh signifikan positif pada pengembalian saham di Inggris, Italia dan Brazil sedangkan pada negara lainnya adalah memiliki pengaruh tidak signifikan.…”
Section: Pendahuluanunclassified
“…Peningkatan kasus sembuh dapat menjadi sentiment positif bagi masyarakat karena semakin meningkatnya kasus sembuh, maka pemerintah akan semakin melonggarkan kebijakan untuk menekan penyebaran kasus COVID-19 dan lebih berfokus pada pemulihan perekonomian. Penelitian yang dilakukan oleh (Basuony, Bouaddi, Ali & Emadeldeen, 2021) menjelaskan bahwa Kasus Kematian COVID-19 memiliki hubungan negatif dengan pengembalian saham di Italia dan hubungan tidak signifikan pada negara lainnya. Kasus Sembuh COVID-19 memiliki pengaruh signifikan positif pada pengembalian saham di Inggris, Italia dan Brazil sedangkan pada negara lainnya adalah memiliki pengaruh tidak signifikan.…”
Section: Adaptive Market Hypothesisunclassified
See 1 more Smart Citation
“…Harjoto et al (2020) found that the pandemic caused a negative shock to the global stock markets, especially in emerging markets and for small firms, whereas Baker et al (2020) found that restrictions on commercial activity and the provision of social distancing due to lockdowns affected the service sector. Basuony et al (2021) found that the impact of COVID-19 was not symmetric across markets. Ozkan (2021) investigated the impact of the COVID-19 pandemic on stock market efficiency for six hard-hit developed countries from 29 January 2019 to 25 January 2021 using the wild bootstrap automatic variance ratio test.…”
Section: Introductionmentioning
confidence: 95%